Revitalizing Local Wisdom in Digital Classrooms to Foster Innovative and Meaningful Learning Experiences - İbrahim Tolga Çelik (PT. Islamic Research Publisher, 2025)
This study investigates the revitalization of local wisdom in digital classrooms as a strategy to foster innovative and meaningful learning experiences. The research aims to explore how indigenous knowledge can be effectively integrated into modern educational technology, enhancing both cultural awareness and pedagogical creativity. Specifically, it seeks to identify the mechanisms through which local cultural elements can enrich digital learning processes, and how these practices influence students’ engagement, critical thinking, and problem-solving abilities. A qualitative case study design was employed, involving classroom observations, semi-structured interviews with educators and students, and content analysis of digital learning materials. Data were analyzed using thematic coding to uncover patterns and insights regarding the integration of local wisdom into digital pedagogies. Findings indicate that embedding local cultural knowledge in digital learning environments significantly improves student motivation and participation. The study also shows that culturally contextualized digital activities encourage collaborative learning, creative expression, and the application of traditional values in contemporary problem-solving. Furthermore, educators reported enhanced satisfaction and perceived effectiveness in teaching when local wisdom was systematically incorporated into lesson design. The study contributes to the field of educational technology by presenting a conceptual framework for integrating indigenous knowledge into digital classrooms, bridging traditional cultural practices and modern pedagogical approaches. This framework provides practical guidance for educators, curriculum developers, and policymakers aiming to create learning environments that are not only technologically advanced but also culturally responsive and innovation-oriented. The findings underscore the importance of preserving local wisdom in education while leveraging digital tools to make learning experiences more meaningful, engaging, and socially relevant.